Study of effects of combined spinal epidural analgesia on the course of labour and feto maternal outcome in comparison with the parturients receiving no analgesia - Bembalgi, Shoba; Kallapur, Basavaraj; S., Prasad; M., Shruthi; Amble, Amit S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The study was aimed to evaluate the effects of combined spinal epidural analgesia on the duration and outcome of labour in nulliparous parturients in comparison with parturients not receiving any analgesia. Methods: It is a prospective clinical study. The present study was carried out in the labour ward, KIMS Hubli. Nulliparous parturients in early active labour were divided into two groups. CSE group (n=40) and non CSE group. In present study CSE was performed with intrathecal 1.25mg of levobupivacaine with 25mcg fentanyl initially and this was followed by epidural boluses of 10ml of 0.0625% Levobupivacaine with 2mcg/ml fentanyl through the epidural catheter whenever the patients’ pain score is more than 4. Results: Mean duration of active labour was 139+/-41.2min in CSE group and 251.1+/-57.9 min in non CSE group. The rate of cervical dilatation was 2.63+/-0.66cm/hr. in CSE group as compared to 1.45+/-0.38cm/hr in non CSE group. The duration of second stage of labour was similar in both groups. The spontaneous vaginal deliveries was77.5% in CSE group as compared to 79.5% in non CSE group. Assisted vaginal deliveries were 15% in combined spinal epidural analgesia group compared to 10.3% in non CSE group which was statistically insignificant. LSCS was 7.5% in control CSE group compared to 10.3% in non CSE group. Maternal satisfaction was excellent in majority of parturients in CSE group. The perinatal outcome was not affected in CSE group. The incidence of complications were very minimal in present study. Conclusions: Authors concluded that combined spinal epidural analgesia provides safe and excellent analgesia with no significant increase in the caesarean section and instrumental delivery rates. In addition, CSE decreases the duration of first stage of labour with no effect on perinatal outcome.